Внешние эллипсоидальные аппроксимации множеств достижимости динамических систем - Бабий, Н.А.; Волосов, В.В.; Шевченко, В.Н. (Кибернетика и вычислительная техника, 2014)
Рассмотрен класс дискретных и непрерывных динамических систем (ДС) с ограниченным возмущением. С использованием техники выпуклого анализа найдены уравнения эволюции эллипсоидов, содержащих множество достижимости ДС. Методом функций Ляпунова получена оценка предельного множества ДС. Для системы управления угловым движением твердого тела проведено сопоставление эллипсоидальных оценок предельного множества и асимптотики множества достижимости. Розглянуто клас дискретних і неперервних динамічних систем (ДС) з обмеженим зовнішнім збуренням. З використанням техніки опуклого аналізу отримано рівняння еволюції еліпсоїдів, які містять множину досяжності ДС. Методом функцій Ляпунова отримано оцінку граничної множини ДС. Для системи керування кутовим рухом твердого тіла проведено співставлення еліпсоїдальних оцінок граничної множини й асимптотики множини досяжності. The purpose: Development of constructive methods for constructing ellipsoidal estimates of reachable sets DS and obtaining guaranteed accuracy estimates of DS control systems in steady mode. Results: Ellipsoidal estimates reachable sets of continuous and discrete DS obtained according to consistent methodological approach based on using the support functions apparatus of convex sets and methods of mathematical programming. The proposed methods are locally optimal by matrix trace criteria of estimating ellipsoids. Ellipsoidal estimates of limit sets of continuous linear DS with bounded external disturbances are obtained based on use known General direct Lyapunov method. As exemplified by control of a solid body angular motion, ellipsoidal estimates of limit sets and asymptotic estimates of reachable sets are complementary. The intersection of these sets is an improved estimate of steering control accuracy in the steady mode